“Could You Work in My Team?”: Exploring How Professional Clinical Role Expectations Influence Decision-Making of Assessors During Exit-Level Medical School OSCEs - Malau-Aduli, Bunmi S.; Hays, Richard B.; D'Souza, Karen; Jones, Karina; Saad, Shannon; Celenza, Antonio; Turner, Richard; Smith, Jane; Ward, Helena; Schlipalius, Michelle; Murphy, Rinki; Garg, Nidhi (Frontiers in Medicine, 2022)
Decision-making in clinical assessment, such as exit-level medical school Objective Structured Clinical Examinations (OSCEs), is complex. This study utilised an empirical phenomenological qualitative approach with thematic analysis to explore OSCE assessors’ perceptions of the concept of a ‘prototypical intern’ expressed during focus group discussions. Topics discussed included the concept of a prototypical intern, qualities to be assessed, and approaches to clinical assessment decision-making. The thematic analysis was then applied to a theoretical framework (Cultural Historical Activity Theory – CHAT) that explored the complexity of making assessment decisions amidst potentially contradicting pressures from academic and clinical perspectives. Ten Australasian medical schools were involved with 15 experienced and five less experienced assessors participating. Thematic analysis of the data revealed four major themes in relation to how the prototypical intern concept influences clinical assessors’ judgements: (a) Suitability of marking rubric based on assessor characteristics and expectations; (b) Competence as final year student versus performance as a prototypical intern; (c) Safety, trustworthiness and reliability as constructs requiring assessment and (d) Contradictions in decision making process due to assessor differences. These themes mapped well within the interaction between two proposed activity systems in the CHAT model: academic and clinical. More clinically engaged and more experienced assessors tend to fall back on a heuristic, mental construct of a ‘prototypical intern’, to calibrate judgements, particularly, in difficult situations. Further research is needed to explore whether consensus on desirable intern qualities and their inclusion into OSCE marksheets decreases the cognitive load and increases the validity of assessor decision making.